A physical interpretation of recent tropical cyclone postlandfall decay - Phillipson,LM; Toumi,R (Geophysical Research Letters, 2021)
The decay of landfalling tropical cyclones is important to the damage caused. We examine a simple physically based decay model of maximum surface winds driven by frictional turbulent drag and a modification accounting for partial to complete land roughness. The model fits an algebraic decay with a parameter determined by the ratio of the surface drag coefficient to the effective vortex depth. This parameter has been decreasing from 1980 to 2018. There is also a global mean increase of wind speed 24 h after landfall of +1.13 m/s per decade. We cannot exclude the possibility that this trend is driven by the initial wind speed increase, but it is most likely due to a slowing of the decay. This weaker decay amounts to an additional 7 h of gale force winds for a typical Category 1 at landfall.